Metastatic Adenocarcinoma Cerebrum Mimicking Tuberculoma in Pregnancy: A Case Report with Review of literature - Awasthi, Rahul; Jain, Nilesh; Rege, Shrikant; Iyengar, Raghwan; Songara, Abhishek (Indian Journal of Neurosurgery, 2017)
Brain tumors in pregnancy are rare phenomenon with variable outcomes. We present a case of adenocarcinoma cerebrum originated from the lung in a 24-year-old primigravida woman. The patient was operated successfully, and 6-month postoperative period was uneventful. A female child was born with cesarean section at full term.
Keywords: pregnancy; adenocarcinoma; metastasis